Implementing a decentralized opioid overdose prevention strategy in Mexico, a pending public policy issue - Raúl Bejarano Romero; Jaime Arredondo Sánchez-Lira; Said Slim Pasaran; Alfonso Chávez Rivera; Lourdes Angulo Corral; Anabel Salimian; Jorge J. Romero Vadilllo; David Goodman-Meza (The Lancet Regional Health. Americas, 2023)
Summary: The public health crisis due to opioid overdose is worsening in Mexico’s northern region due to the introduction of illicitly manufactured fentanyl into the local drug supply. Though there is an increase in overdose deaths, there is no accurate report of overdoses by Mexican government agencies and no comprehensive opioid overdose prevention strategy. There is currently only an anti-drug marketing strategy which is likely insufficient to mitigate the growing epidemic. In order to address the growing opioid overdose crisis in the country, it is necessary to create and implement a decentralized prevention strategy, that includes naloxone distribution, expanded treatment services in regions most in need, and create active dialogue with community organisations already implementing harm reduction actions. Decisive action must be taken by the Mexican government to ensure the health and wellbeing of the Mexican citizens, especially those at high risk for opioid overdose.